WAGE TAX ACCOUNTING IN THE AGRICULTURAL ENTERPRISES - Bondarchuk, N.V. (The actual problems of regional economy development, 2017)
The article aims to determine the order of accounting taxation wage and directions of its improvement in the agricultural enterprise. It was identified, that the accuracy of calculation of the related to wage amounts of mandatory payments to the budget depends on the correct definition of the amount of wage and its structure. It is noted, that in our country income tax from individuals and military collection is deducted from wages. Single social contributions is charged on the labor remuneration fund. Main accounts which are used for displaying in accounting for taxation of wages and basic accounting records were shown. It was stated, that taxation of wages, which is less than the minimum, despite the simple theoretical explanation, on practice is very time-consuming process which requires a certain sequence, accuracy and attentiveness. To improve the process of wages taxation we propose to calculate the amounts of the Single social contribution charged on wage which is less than minimum, in a specially developed form, which will help to simplify calculation of the Single social contribution on wage, which is less than minimum, that will help to improve wage tax accounting.